PENGOLAHAN MOTIF DARI INSPIRASI ORNAMEN TAMANSARI KERATON YOGYAKARTA - Dea Rahma Andini; Morinta Rosandini (Jurusan Seni Rupa ISBI Bandung, 2017)
Tamansari Keraton in Yogyakarta is one of cultural heritage in Indonesia with high traditional values. Today, Tamansari is chosen as a tourist destination by Indonesian government. This place was a resort for the Keraton King and his relatives. In 2004, Tamansari has been pronounced by The World Monument Fund as one of the 100 endangered sites. By looking at that phenomena, re-introduction is severely needed to keep the existence of the structure. This research uses qualitative method through direct observation on Tamansari structure, literature studies, and experiment method. Re-introduction was done by introducing Tamansari Keraton through fashion media by applying its ornaments and architectural silhouette of the structure into ready-to-wear clothing referring back to 1950’s vintage fashion. The techniques applied in design process are stylation, 1 step and ½ step repetition, and computerization which later is applied to digital printing technique. The colours used are adjusted to the colour of the structure to reinforce the purpose of re-introducing f Tamansari Keraton to the public. By doing so, it is expected that they are getting familiar to Tamansari Keraton.Keywords: Digital Printing, Ready-To-Wear, Tamansari Keraton___________________________________________________________________ Tamansari Keraton Yogyakarta merupakan salah satu warisan budaya Indonesia yang memiliki nilai budaya yang tinggi. Kini, Tamansari telah dijadikan sebagai tempat pariwisata oleh pemerintah. Tempat ini dahulu berfungsi sebagai tempat peristirahatan untuk raja Keraton dan kerabat. Pada tahun 2004, Tamansari telah ditetapkan oleh World Monument Fund sebagai salah satu dari 100 situs yang terancam keberadaannya/ terancam punah. Dengan melihat fenomena tersebut, dibutuhkan adanya upaya pengenalan kembali agar dapat menjaga eksistensi bangunan tersebut.Penelitian ini dilakukan dengan metode kualitatif melalui observasi langsung terhadap bangunan Tamansari, studi literatur, dan metode eksperimen. Upaya pengenalan dilakukan dengan cara memperkenalkan Tamansari Keraton melalui media fesyen dengan mengambil ornamen dan siluet struktur bangunan ke dalam busana ready-to-wear yang mengacu pada fesyen vintage tahun 1950. Warna yang digunakan pun disesuaikan dengan warna bangunan agar dapat lebih mengenalkan Tamansari Keraton kepada masyarakat, sehingga tujuan untuk memperkenalkan bangunan dapat terasa.Kata Kunci: Digital Printing, Tamansari Keraton, Vintage